Synthesis and Characterization of Metal(II) Complexes with Macrocyclic Ligand, 1,4,5,7,8,11,12,14-octaaza-tetraoxo-6,13-dithio-1,4,5,7,8,11,12,14- octahydrocyclotetradecane - Jha, R.R.; Sahu, N. (Asian Journal of Chemistry, 2010)
Metal complexes of the type, [ML(H2O)2]X2 [M = Mn(II), Fe(II) and Zn(II), X = Cl¯, Br¯ & NO3¯] have been synthesized with macrocyclic ligand, 1,4,5,7,8,11,12,14-octaazatetraoxo- 6,13-dithio-1,4,5,7,8,11,12,14-octahydrocyclotetradecane (OTDCT). The complexes are characterized by elemental analysis, conductivity measurements, electronic spectral data and magnetic susceptibility value. The ligand has been found to coordinate to metal ion through four imido nitrogen atoms. Further two coordination sites of metal ions are satisfied by the oxygen of water molecules. Thermal analysis of complexes show similar pattern of decomposition. Weight loss ca. 190 ºC in one step with exothermal peak in DTA curve may be attiributed to loss of two water coordinated molecules.